To what extent do we learn from past epidemics: a mobile phone survey of selected villages in Liberia - Elisa Maria Maffioli; Daisey Yu (Inishmore Laser Scientific Publishing Ltd, 2024)
# Background Epidemics remain a major threat, impacting lives around the globe. We ask whether and to what extent individuals learn from past epidemics in Liberia, a country affected by both the 2014-2016 Ebola Virus Disease and COVID-19. # Methods We explored the association between being exposed to the 2014-2016 Ebola epidemic and measures of beliefs, intentions, and behavior during COVID-19. We interviewed 600 respondents three times over seven years, sampled by an initial list of 2,265 respondents in 571 villages across all of Liberia selected through Random Digit Dialing (RDD) in 2015-2016. We used an Ordinary Least Square (OLS) model, controlling for county fixed effects and a set of socio-demographic and economic covariates. # Results Because of the selection among individuals with mobile phones, most respondents were male, educated, and were more likely to be from urban areas and wealthy. They were, on average, 33.9 (SD=10.4) years old, 66% were Catholic, and only 23% were unemployed. 22.8% of respondents reported that they knew someone in their community who got or was suspected of having Ebola; 13.7% were exposed to COVID-19, while 4.5% were exposed to both epidemics. We found that those exposed to Ebola were less likely to have wrong beliefs about the virus and how to cure it; they were also more likely to state that they would go to the health facility for important needs such as birth delivery and child routine vaccination; and, they were more likely to get vaccinated during COVID-19. The findings are primarily driven by individuals with low trust in the government. # Conclusions This research suggests that individuals who experience a previous epidemic learned from it and might be more responsive to correct information and better respond to a future one. This has policy implications for patient education and awareness campaigns during the next epidemic.